Phytochemicals: potential alternative strategy to fight Salmonella enterica serovar Typhimurium - Almuzaini, Abdulaziz M. (Frontiers in Veterinary Science, 2023)
The rise of multidrug resistant (MDR) microorganisms is a great hazard worldwide and has made it difficult to treat many infectious diseases adequately. One of the most prevalent causes of outbreaks of foodborne illness worldwide is Salmonella. The ability of this and other harmful bacteria to withstand antibiotics has recently proven crucial to their effective control. Since the beginning of time, herbal medicines and phytochemicals have been employed for their potent antibacterial action and there is a growing trend towards the production of plant based natural products for the prevention and treatment of pathogenic infections. Numerous phytochemicals have been proved effective against the molecular determinants responsible for attaining the drug resistance in pathogens like efflux pumps, membrane proteins, bacterial cell communications and biofilms. The medicinal plants having antibacterial activity and antibiotics combination with phytochemicals have shown synergetic activity against Salmonella typhimurium. The inhibitory effects of tannins on rumen proteolytic bacteria can be exploited in ruminant nutrition. An improved control of the rumen ecology and practical use of this feed additive technology in livestock production will be made possible by a better knowledge of the modulatory effects of phytochemicals on the rumen microbial populations in combination with fermentation. This review focuses on the development of antibacterial resistance in salmonella, mechanism of action of phytochemicals and use of plant derived medicinal plants against S. typhimurium, and the advances and potential future applications of phytochemicals in the fight against resistant Salmonella typhimurium.